OILADAGI AVLODLARARO MUNOSABATLARNING IJTIMOIY – FALSAFIY JIHATLARI - Mamarayemova Guljahon Farhodovna, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article studies intergenerational relations in the family from a socio-philosophical perspective. It considers historical experience, the evolution of social institutions, the transformation of people, and the specific characteristics of generations in the modern world.